On the problem of the law of international organizations - M.N. Rajabov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper considers the views of scientists on the position of the law of international organizations in the general system of law. The main stages in the development of the law of international organizations as an independent branch of the public international law have been analyzed. In particular, it has been noted that the law of international organizations is understood in two ways – in the broad and narrow sense. In the broad sense, the law of international organizations is a branch that regulates public relations in the field concerning the legal status and activities of international organizations, international conferences, international institutions, and international organs. In the narrow sense, the law of international organizations is a branch that regulates only the legal status and activities of international organizations. The concept of the law of international organizations in the narrow sense has been supported. It has been proved that this judgment is close to the reality and relates the regulation of international interstate and non-state relations to its subject. The law of international organizations as an independent branch of international public law has been analyzed in relation to the national law and foreign law (private international law).